Cafeteria‐style feeding trials provide new insights into the diet and nutritional strategies of the black snub‐nosed monkey (Rhinopithecus strykeri): Implications for conservation. Issue 3 (25th February 2020) - Yang, Yin; Li, Qihua; Garber, Paul A.; Grueter, Cyril C.; Ren, Guopeng; Wang, Xinwen; Huang, Zhipang; Xiang, Zuofu; Xiao, Wen; Behie, Alison
Abstract: Anthropogenic changes and fragmentation of natural habitats often exert a negative effect on resource availability and distribution, and the nutritional ecology and feeding behavior of nonhuman primates. The goals of this study are to examine food choice and to identify the nutritional profile of foods consumed by the Critically Endangered black snub‐nosed monkey ( Rhinopithecus strykeri ). To accomplish our study goals, we presented cafeteria‐style feeding trials of fresh food items collected in the home range of wild black snub‐nosed monkeys to the only two captive R. strykeri, and compared the nutritional profiles of the leafy foods (buds, young, and mature leaves, 100 items from 70 plant species) selected with those avoided (54 items from 48 plant species). Overall, the results indicate that captive R. strykeri selected foods that were higher in moisture (Mo; 77.7%), crude protein (CP; 21.2%), total nonstructural carbohydrates (TNC; 34.9%), and phosphorus (P; 0.37%) while tending to avoid foods with a neutral detergent fiber (NDF) content of greater than 46.8%. Leaves collected in autumn and selected by the monkeys were characterized by a slightly higher amount of metabolizable energy (ME) than those rejected (1, 350 kJ/100 g vs. 1, 268 kJ/100 g). In contrast, the protein content of foods collected and consumed during the spring was greater (22.9%) than in autumn (16.4%). Random Forests modeling, an ensemble learning method, indicated that the proportion of Mo, NDF, ME, CP, P, and TNC were among the most important factors in predicting which items were consumed by the captive R. strykeri during spring and autumn. On the basis of the nutritional profile of foods consumed across the two seasons, we identified 18 nutrient‐rich native plant species that we recommend for use in ex‐ and in‐situ conservation management and reforestation programs to provide long‐term access to a nutritionally adequate diet. Abstract : A female black snub‐nosed monkey ( Rhinopithecus strykeri ) fed on leaves of Actinidia venosa in a cafeteria‐style feeding trial at the Yaojiaping Wildlife Rescue Centre in the Gaoligong Mountains National Nature Reserve, China (Photo by Yin Yang). Research Highlights: We used cafeteria‐feeding trails to study patterns of nutrient intake in the only two black snub‐nosed monkeys ( Rhinopithecus strykeri ), a critically endangered primate, in captivity. We collected foods from the species' natural habitat and compared the nutrient content of 100 leaf items consumed ( n = 70 plant species) with the nutrient content of 54 leaf items ( n = 48 plant species) that the monkeys chose not to consume. The results indicate that captive R. strykeri selected leaves that were high in moisture (Mo), crude protein (CP), total nonstructural carbohydrates (TNC), and phosphorus (P) while tending to avoid leaves with a high neutral detergent fiber (NDF) content. Random Forests modeling indicated that the proportion of Mo, CP, NDF, metabolizable energy, P, and TNC are among the most important factors in predicting R. strykeri 's feeding selection on leaf items. On the basis of the nutritional profile of foods consumed by R. strykeri, 18 nutrient‐rich native plant species were identified and recommended to be used in ex‐ and in‐situ conservation programs for this threatened species.